Metabolic responses to sago and soy supplementations during endurance cycling performance in the heat - Tarmast, D.; Ghosh, A. K.; Chen, C. K. (International Journal of Applied Exercise Physiology, 2017)
This study examined the effects of Sago (Sa), Soy (So), combined isocaloric Sago+Soy (SS) supplementations during cycling on metabolic responses as compared to placebo (P) in the heat (31°C, 70% relative humidity). Twelve wellâ€"trained male cyclists (Age: 19.0±5.6 yr, Height: 170.8±7.6 cm, Wight: 60.1±11.2 kg, and VO2max: 56.5±6.5 mL/kg.min) participated in four experimental trials. The design of the trials was a randomized single-blind, placebo-controlled crossover trail comprising 90 min of steady-state cycling on an ergometer at 60% of VO2max followed by a 20-km time trial performance (TT). The participants of the study were supplemented 5 times at 0, 20, 40, 60, and 80 minutes during the steadyâ€"state cycling. Sa, So, and SS supplements provided 7.5% Sago, 7.5% Soy, and 6.0% Sago + 1.5% Soy respectively. Plasma glucose concentrations (PG) reached a peak at 60 min after ingestion of Sa and SS as compared to baseline. At the end of the TT, PG reduced significantly to the baseline level. Plasma insulin concentrations (PI) increased in all trials, but reduced gradually to the baseline level. The concentration of plasma free fatty acids (FFA) increased gradually during the steady state cycling and TT, and FFA was significantly higher in the P and So than the Sa and SS trials. At the end of the steady state cycling, the plasma lactate concentration (LACT) reached its lowest concentrations and at the end of the TT was enhanced significantly in all trials. These results suggest that sago and soy supplements increase the PG and PI during endurance exercise in the heat. These data add to the growing body of knowledge concerning endurance athletes glycemic and insulinemic responses to carbohydrate consumptions during exercise in the heat.